The effects of two surgical gowning and gloving methods on the extent of contamination of surgical team members' gowns and gloves: A single-blind controlled trial - Foziye Hamoole Tahmasebi; Saeid Amini Rarani; Ahmad Ghadami (Kashan University of Medical Sciences, 2023)
Background: The method used to wear the surgical gown and gloves has a critical role in the extent of surgical site contamination.Objectives: The purpose of this study was to compare the effect of gown and gloves wearing in the integrated and closed methods on the extent of contamination of surgical team members' gowns and gloves. Methods: A single-blind controlled trial was conducted with 70 eligible surgical staff who were randomly assigned to two groups of 35. The intervention group wore sterile, integrated gown-glove units, whereas the control group wore separate gowns and gloves using the closed technique. Glitterbug fluorescent powder was used to measure contamination. An ultraviolet flashlight was used to make the Glitterbug powder visible. Participants in both groups wore their gowns and gloves after dipping their hands in fluorescent powder. After one hour of the surgery, the gowns and gloves were removed from the body, a mobile phone was used to take photos of the areas containing powder, and ImageJ software was used to measure the area of contamination. The independent samples t-tests and chi-square test were used to analyze the data.Results: The contaminated area of gloves was 0.06±0.24 mm2 for the integrated gown-glove unit method and 2.26± 5.87 mm2 for the closed gown and gloves wearing method (P= 0.03). The contaminated area of the gown was zero for the integrated method and 3.06±7.57 mm2 for the closed method (P= 0.02).Conclusion: The extent of contamination was less when using the integrated gown-glove unit than the closed method. The surgical staff are recommended to use integrated gown-glove units to reduce the risk of contamination of gowns and gloves used for surgery.